Модуси морфоструктурної мінливості пагонів видів роду Dracaena Vand. ex L. (Dracaenaceae Salisb.) - Maltsov, I.Yu. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
In the article the patterns of development and morpholo gical structure of shoots of 9 Dracaena Vand. ex L. species were analyzed. The moduses of morphostructural adaptation of shoots of species studied were determined.